2019
DOI: 10.4314/jasem.v23i3.17
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of cow horn as filler in an epoxy composite

Abstract: This study focuses on assessment of cow horn as filler in an epoxy composite. A particle-reinforced composite was developed using horn particles (HP) and epoxy resin with filler of varying percentage weight (5%, 10%, 15%, 20%. 25%, 30%, 35%, 40 %) at particle sizes of 100 and 150 μm. The composites were developed by hand lay-up technique with varying process parameters. The properties of the developed composites were examined through tensile, flexural and impact tests. The results showed that the tensile prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…It is therefore a source of animal origin containing keratin which is a protein with an ability to protect the animal against its natural surroundings. As well as a better resistance to chemical actions [7].The keratin used is durable. Organic waste containing this protein can be used as a bio load with no harmful effects [8].…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore a source of animal origin containing keratin which is a protein with an ability to protect the animal against its natural surroundings. As well as a better resistance to chemical actions [7].The keratin used is durable. Organic waste containing this protein can be used as a bio load with no harmful effects [8].…”
Section: Methodsmentioning
confidence: 99%
“…The horn keratin differs significantly from other keratins in that it displays greater energy absorption in the hydrated state as well as significant strain rate dependence in both tension and compression. Cow horn particle-reinforced epoxy resin composites with varying filler percentages (5,10,15,20,25,30,35, and 40 wt%) and particle sizes of 100 and 150 m made using the manual layup approach were examined by Ambali et al [13]. The study's findings showed that the tensile properties of the filler increased to a particular level and then reduced when cow horn was added.…”
Section: Introductionmentioning
confidence: 99%
“…As for the bamboo particles, they were the lowest compared to the rest of the additives, and this is due to the shape of the needle-shaped particles, which causes an increase in the stress concentration, in addition to that it causes the expansion of cracks, which leads to a reduction and deterioration in the mechanical properties in the case of an increase in the ratio of more than 6%wt. We note that the tensile strength decreased at the beginning when adding 2% of animal horn powder and that because of the possibility of the presence of microscopic defects resulting from the manufacturing process and caused by the agglomeration of the grains or the presence of microscopic cracks on the surface as indicated by the researchers ambali and Ain [18,19]. Fig.…”
Section: Mechanical Tests Results For Composite Materials Tensile Testmentioning
confidence: 70%
“…Ambali et.al. studied the use of animal horns powder of sizes (100 and 150) µm as a material for reinforcing with epoxy and studied the properties of tensile, bending, and impact, where the results showed that the particles with particle size (100 µm) gave better results compared to the particle size (150 µm) [18]. Ain et.al.…”
Section: Introductionmentioning
confidence: 99%